(untitled) (Communications in Mathematical Research, 2019)
Let H be a finite-dimensional weak Hopf algebra over a field k and A an associative algebra, and A#_σH a weak crossed product. In this paper, a spectral sequence for Ext is constructed which yields an estimate for cotorsion dimension of A#_σH in terms of the corresponding data for H and A.